Hubungan Tebal Lemak Tubuh dengan Panjang Siklus Menstruasi - Annif Munjidah (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2016)
Factors affecting the menstrual cycle in women are: age, psychological, physical (heredity, nutritional status, and environment) and drugs. So far, the study on the menstrual cycle is only seen from the factors of nutritional status through the upper arm circumference and BMI (Body Mass Index). This situation encouraged researchers to conduct a study on the menstrual cycle length from nutritional factors as seen from body fat thickness.This study aims to analyze the correlation of body fat thickness and menstrual cycle length on the students. The study used an observational analytic with cross sectional approach. The population was all of the students in the first level of DIII Midwifery Department of Nursing and Midwifery Faculty of UNUSA who had regular menstrual cycles and do not take antidepressant drugs/contraceptive device. The sample was mostly students using simple random sampling. The total of the sample was 72 people. The test analysis was done by a moment product (alpha 0.05). The result of the study showed that p value is 0,039 < 0,05. There was a correlation between the body fat thickness and menstrual cycle length of the first level students of DIII Midwifery Department of Nursing and Midwifery Faculty of UNUSA. The conclusion of this study was the thicker of the student's body fat the longer their menstrual cycles. For the health workers, they can provide counseling on female adolescents about reproductive health especially menstruation and the risk of fat in the body.